Do local para o nacional: o orçamento participativo e as novas práticas políticas petistas - Souza, Luciana Andressa Martins de (2010)
The central objective of this thesis was to verify in which manner participatory budgeting was transformed into a political strategy of the PT (Worker s Party) for the party be consolidated into a viable option for federal government, keeping in mind the growth of the party in elections subsequent to the successful experiences of local governments that adopted participatory reforms. As a basis we took the premise of Panebianco (2005) concerning institutional changes to explain how programmatic changes endured by the PT impacted the consolidation of these participatory politics. The secondary objective was to analyze whether or not the implantation of participatory budgeting in drafting local politics contributes to the change of local political practices, especially verified by the introduction of this new participatory arrangement in the relationship between local executive and legislative branches. To reach this objective, we compared the institutional design of three experiences in participatory budgeting that are similar in various ways, but are distinguishable by the results produced by these participatory institutions. This analysis is theoretically based on the comparative institutional approach and the conjectures of Peter Evans (1995, 2004b) who departs from contextual differences and searches for regularities or analyzes, rather, the nature and the role of these participatory mechanisms in comparative terms. In sum, we concluded that participatory budgeting was a form of learning local and national policies and politics for the PT.